A parameter estimation method for a simplified electrochemical model for Li-ion batteries. (10th June 2018) - Li, Junfu; Wang, Lixin; Lyu, Chao; Liu, Enhui; Xing, Yinjiao; Pecht, Michael
Abstract: Traditional electrochemical algorithms are too complex for use in real-time battery management systems (BMSs). Determination of parameters and implementation of algorithms are the key challenges for electrochemical models for Li-ion batteries. This paper develops a simplified electrochemical model that incorporates open-circuit voltage, liquid-phase diffusion, reaction polarization, and ohmic polarization, and uses a fast operating test to identify all the parameters to solve these challenges. The model is then implemented and compared against experimental measurements. Validations of parameter estimation and charge/discharge behaviors indicate that the developed parameter estimation method for the electrochemical model is effective. With this model and parameter estimation technique, electrochemical model-based state of charge (SOC) estimation can be realized online and can provide accurate results. Highlights: A simplified electrochemical model is developed. A test is developed for identifying all parameters in less than 8 h. Parameters are obtained based on different response times of internal processes. Validations of the developed parameter estimation method indicate its effectiveness. The developed model has a good computational efficiency.